Jason Lezak again and again - linear mixed modelling analysis of change-over times in relay swimming races - Fischer, S.; Braun, C.; Kibele, A. (Journal of Sports Sciences, 2019)
The aim of this study was to examine the importance of the change-over time in swimming relay races. Top-class international 4 x 100 m freestyle races were analysed across a 10-year period including three Olympic Games and five European and World Championships. A total of 220 swimmers (116 female, 104 male) were included in this study with an average participation of 1.7 ± 1.2 races. To consider such repeated measurements and other factors (e.g., ranking in the relay race, position in the relay team) linear mixed models for longitudinal data were used for the statistical evaluation. Our results showed significantly longer change-over times for male medallists (0.23 ± 0.08 s) than non-medallists (0.20 ± 0.09 s) which reflects a very likely effect (94.2%). Furthermore, there were significant differences in change-over times between female and male swimmers depending on the current race positions. In total, the influence of change-over time on the final performance in 4 x 100-m freestyle relay appears to be overrated in previous studies.